2023
DOI: 10.3390/diagnostics13030443
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Extracellular Vesicles in Chronic Kidney Disease: From Bench to Bedside?

Abstract: Extracellular vesicles are a diverse group of particles that include exosomes, microvesicles, and apoptotic bodies and are defined by size, composition, site of origin, and density. They incorporate various bioactive molecules from their cell of origin during formation, such as soluble proteins, membrane receptors, nucleic acids (mRNAs and miRNAs), and lipids, which can then be transferred to target cells. Extracellular vesicles/exosomes have been extensively studied as a critical factor in pathophysiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 167 publications
0
11
0
Order By: Relevance
“…uE are produced by the kidney and pass through almost all kidney cell types. Additionally, uE contain miRNAs, which can be remarkably stable and easily obtained, providing readily available sources in the clinical setting for diagnosis and monitoring, serving as biomarkers for kidney diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…uE are produced by the kidney and pass through almost all kidney cell types. Additionally, uE contain miRNAs, which can be remarkably stable and easily obtained, providing readily available sources in the clinical setting for diagnosis and monitoring, serving as biomarkers for kidney diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cargo of EVs secreted by kidney cells can reflect the kidney’s pathophysiology. cEVs and uEVs in CKD and OCKD patients has been shown to carry specific proteins that are related to lipid metabolism, oxidative stress, inflammation, and fibrosis, which are hallmarks of pathology progression ( D et al, 2023 ; Grange and Bussolati, 2022 ) ( Figure 3 ). uEVs and cEVs have been investigated as potential diagnostic tools in CKD.…”
Section: Evs In Kidney Diseasementioning
confidence: 99%
“…It has recently been shown that 3% of the total urinary protein content originates from EVs [ 37 ]. Although urinary EVs serve as a reservoir of biomarkers that come from the kidneys, ureters, urinary bladder, urethra [ 38 ], and prostate [ 39 ], their secretion and reuptake are essential in intercellular communication along the nephron and thus preservation of homeostasis of the urinary tract [ 40 ].…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%